Aggregatibacter actinomycetemcomitans cytolethal distending toxin modulates host phagocytic function - Kim, Taewan J.; Shenker, Bruce J.; MacElroy, Andrew S.; Spradlin, Samuel; Walker, Lisa P.; Boesze-Battaglia, Kathleen (Frontiers in Cellular and Infection Microbiology, 2023)
Cytolethal distending toxins (Cdt) are a family of toxins produced by several human pathogens which infect mucocutaneous tissue and induce inflammatory disease. Human macrophages exposed to Aggregatibacter actinomycetemcomitans (Aa) Cdt respond through canonical and non-canonical inflammasome activation to stimulate cytokine release. The inflammatory response is dependent on PI3K signaling blockade via the toxin’s phosphatidylinositol-3,4,5-triphosphate (PIP3) phosphatase activity; converting PIP3 to phosphatidylinsoitol-3,4-diphosphate (PI3,4P2) thereby depleting PIP3 pools. Phosphoinositides, also play a critical role in phagosome trafficking, serving as binding domains for effector proteins during phagosome maturation and subsequent fusion with lysosomes. We now demonstrate that AaCdt manipulates the phosphoinositide (PI) pools of phagosome membranes and alters Rab5 association. Exposure of macrophages to AaCdt slowed phagosome maturation and decreased phago-lysosome formation, thereby compromising macrophage phagocytic function. Moreover, macrophages exposed to Cdt showed decreased bactericidal capacity leading to increase in Aggregatibacter actinomycetemcomitans survival. Thus, Cdt may contribute to increased susceptibility to bacterial infection. These studies uncover an underexplored aspect of Cdt function and provide new insight into the virulence potential of Cdt in mediating the pathogenesis of disease caused by Cdt-producing organisms such as Aa.